Application of matrix-assisted laser desorption ionization time-of-flight mass spectrometry in the detection of vancomycin-resistant and-susceptible Enterococcus faecium - He, Wei; Lin, Xintong; Chen, Xueqin; Zeng, Liangming; Guo, Xuemin (Frontiers in Microbiology, 2025)
IntroductionIn recent years, the escalating prevalence of Vancomycin-resistant Enterococcus faecium (VREfm) has emerged as a formidable challenge to global healthcare systems. While Matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF MS) has become an indispensable tool for bacterial identification, its potential for rapid discrimination between Vancomycin-susceptible Enterococcus faecium (VSEfm) and VREfm through characteristic peak analysis remains an area of active investigation.MethodsIn this study, we conducted literature search through databases to summarize the distribution of regionally prevalent VSEfm/ VREfm characteristic peaks, and further collected mass spectrometry data from Meizhou People’s Hospital (Guangdong, China) from 2021 to 2024 to explore stable characteristic peaks for both VSEfm and VREfm.ResultsThrough MALDI-TOF MS analysis, we identified stable characteristic peaks for both VSEfm (m/z 3299.95 ± 3.99 and m/z 6605.13 ± 7.28) and VREfm (m/z 3313.01 ± 2.76 and m/z 6631.03 ± 4.38) in the Meizhou region, with their discriminative efficacy validated by ROC curve analysis.DiscussionOur findings not only demonstrate the regional specificity of these characteristic peaks but also establish a robust methodological framework for rapid VSEfm/VREfm differentiation. This advancement holds significant promise for guiding clinical decision-making and controlling VREfm dissemination. Nevertheless, we acknowledge the necessity for ongoing technological refinement to enhance the accuracy and broader applicability of this approach in diverse clinical settings.